Successful resection of cellular angiofibroma in the retroperitoneum by using laparoscopic approach. Issue 3 (22nd July 2019) - Tamura, Taichi; Matsuda, Takeru; Yamashita, Kimihiro; Hasegawa, Hiroshi; Kanaji, Shingo; Oshikiri, Taro; Nakamura, Tetsu; Suzuki, Satoshi; Fukumoto, Takumi; Kakeji, Yoshihiro
Abstract: Retroperitoneal cellular angiofibroma (RCA) is very rare, and the optimal treatment for RCA has not been established. We report the case of RCA in a 58‐year‐old man who underwent curative laparoscopy‐assisted resection. Preoperative computed tomography showed heterogeneous enhancement of the 7 cm diameter tumor in the pelvis. A smaller (2.3 cm) mass was also detected in the small intestine. The preoperative diagnosis was peritoneal metastasis of the gastrointestinal tumor of the small intestine. The pelvic tumor was laparoscopically mobilized from the rectum, the left ureter, and the left internal iliac vessels. The tumor was excised by detachment from the urinary bladder in laparotomy. The pathological diagnosis was RCA. The tumor had not recurred by the 1‐year follow‐up. The laparoscopic approach thus might be useful for resection of RCA.